2005
DOI: 10.2337/diabetes.54.9.2816
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of PAX4 Gene With Type 1 Diabetes in the Finnish and Hungarian Populations

Abstract: We aimed to assess the possible contribution of the PAX4 transcription factor gene to the genetic background of type 1 diabetes. We analyzed four coding polymorphisms of the PAX4 gene in 498 cases with type 1 diabetes and 825 control subjects from Finland and Hungary. All patients were diagnosed under the age of 15 years according to the World Health Organization criteria. All four PAX4 variants (three in exon 9 and one in exon 3) were genotyped using DNA sequencing. In addition, all Finnish subjects were type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In Egyptian children with T1D, the genotypes 02/02, 02/03 were positively associated and the genotypes 03/06, 06/06 were negatively associated with the disease (Pc = 0.01, Pc < 0.001, Pc < 0.001, and Pc = 0.04, respectively) with the highest risk being with the heterozygote DQB1*02/*03 genotype (OR = 10.6) ( Table 3). Similar findings were reported in the United States [44] , Hungary [38] , Romania [37] , and Saudi Arabia [47,48] . The inheritance of HLA genes associated with T1DM would involve the presentation of diabetic autoantigen to autoreactive T-cells, thereby launching a T-cell activation cascade and the subsequent destruction of pancreatic β islet cells [57] .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In Egyptian children with T1D, the genotypes 02/02, 02/03 were positively associated and the genotypes 03/06, 06/06 were negatively associated with the disease (Pc = 0.01, Pc < 0.001, Pc < 0.001, and Pc = 0.04, respectively) with the highest risk being with the heterozygote DQB1*02/*03 genotype (OR = 10.6) ( Table 3). Similar findings were reported in the United States [44] , Hungary [38] , Romania [37] , and Saudi Arabia [47,48] . The inheritance of HLA genes associated with T1DM would involve the presentation of diabetic autoantigen to autoreactive T-cells, thereby launching a T-cell activation cascade and the subsequent destruction of pancreatic β islet cells [57] .…”
supporting
confidence: 86%
“…To the best of our knowledge, the present study is the first to identify a positive association between HLA-DQB1*0202 and T1D (Table 2). DQB1*0201 and DQB1*0302 were positively associated with T1D in various ethnic populations including Asians [34,35] , European [36][37][38][39][40][41][42][43] , and Americans [44][45][46] . Similar results were reported for Arab patients from Saudi Arabia [47,48] , Kuwait [49] , Tunisia [50] , Lebanon [51] , and Israeli [52] .…”
Section: Discussionmentioning
confidence: 99%
“…The A allele of PAX4 rs712701 (1168C4A; P321H) is frequent in the Asians, including Japanese 12 and Han Chinese 15 but is less frequent in the Europeans. 16 A recent genome-wide association study in a Chinese population 17 and a large meta-analysis in East Asian population 18 identified susceptibility loci for T2D near the PAX4. Our group reported that PAX4 mutations cause MODY9 and PAX4 rs2233580 (781G4A; R192H) genotype and allele frequencies were higher in MODY probands and patients with T2D than in patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it would be unexpected to observe significant deviation in both cases and controls, unless the allele is under selection [61]. Attempts to replicate the association in both a large collection of families as well as in a large case-control study failed (P > 0.1), as did casecontrol studies from Finland and Hungary (P > 0.5) [58], and family-based studies in Denmark [57]. Of particular importance, none of the groups that attempted to replicate the association observed significant deviation from the Hardy-Weinberg equilibrium in either cases or controls, suggesting that there may be technical problems with the genotyping assay in the initial report.…”
Section: Pax4mentioning
confidence: 77%
“…However, several readers identified that there was significant deviation of the genotypes from the Hardy-Weinberg equilibrium in both the cases and controls from Switzerland and Germany [57][58][59][60]. Deviation from the Hardy-Weinberg equilibrium may result from violations of any of the assumptions (including recent admixture, selection, migration) and is also commonly used as a quality control measure for genotyping assays.…”
Section: Pax4mentioning
confidence: 96%